ASPEK TEKNIS PENGEMBANGAN KARYA ARSITEKTURAL DI METAVERSE - Ridwan Sanjaya (JoDA Journal of Digital Architecture, 2022)
The term Metaverse has become viral since Mark Zuckerberg introduced it when the company name changed from Facebook to Meta. The illustration video made to explain to the public has succeeded in shaping the image of Metaverse as the development of Virtual Reality technology. Although other companies have different definitions of Metaverse with Augmented Reality technology at its core, Mixed Reality technology is predicted to unite both technologies. The contents in the Metaverse also need to be prepared to fill the virtual world when the ecosystem is successfully formed. Architectural creations as one of the contents have the opportunity to be created and traded as NFT in the metaverse. This paper explores the business and technical aspects that need to be done in the development of architectural creations in the metaverse.